Renovation and adaptation of the historic Olsztyn Purification House Bet Tahara into a public utility building = Renowacja i adaptacja zabytkowego olsztyńskiego Domu Oczyszczeń Bet Tahara na budynek użyteczności publicznej - Deja, Barbara Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The historic Jewish Purification House Bet Tahara was erected in Olsztyn in 1913 on the basis of the debut design of Erich Mendelsohn, a world-famous architect born in Olsztyn. The most valuable element of the building is a self-supporting pyramid vault above a mourning hall.
Keywords: renowacja obiektów; adaptacja; Żydowski Dom Oczyszczeń; budynek użyteczności publicznej; historic building renovation; adaptation; Jewish Purification House; public utility building